Provenance of cretaceous sediments in the West Kunlun piedmont belt and implications for tectonic evolutionary events - Gao, Yang; Jiang, Lin; Chen, Weiyan; Jiang, Fujie; Dong, Hongkui; Zhao, Wen; Dong, Changyu; Feng, Yingqi (Frontiers in Earth Science, 2024)
The West Kunlun orogenic belt located in the northwestern margin of the Qinghai-Tibet Plateau is an important record of the formation and northward extension of the plateau, but the current research mainly focuses on the tectonic activities of the Cenozoic era, and there is still considerable controversy regarding the formation and evolutionary history of pre-Cenozoic orogenic belts. This study focuses on Cretaceous sandstone samples from the Kedong region in the piedmont belt of the West Kunlun orogenic belt. U-Pb geochronological analysis was performed on 200 detrital zircon grains from the core samples. Combined with stratigraphic data and previous research, the main provenance direction was investigated to constrain the tectonic evolutionary history of the orogenic belt's peripheral regions. The results show that the detrital zircons are aged from 290-208Ma, 520-310Ma, 810-580Ma, 1400-880Ma and 2548-1730Ma, reflecting the complexity of provenance in this area. Based on a comprehensive analysis of the characteristics of igneous rocks, zircon age composition, and stratigraphic conditions in potential source areas, it is concluded that the primary source regions include the East Kunlun orogenic belt and the North and South Kunlun terranes, with a low likelihood of contributions from within the Tarim Basin. The evolution of the West Kunlun orogenic belt can generally be divided into two opening and two closing phases. The detrital zircon ages predominantly exhibit two peak values at 259 Ma and 459 Ma, respectively representing the ages of transition from oceanic crust subduction to continent-continent collision for the Paleo-Tethys Ocean and the Proto-Tethys Ocean. Additionally, there is a temporal gap between the evolution of the Proto-Tethys Ocean and the Paleo-Tethys Ocean. The Triassic period marks a transitional phase in tectonic evolution, shifting into an intracontinental evolutionary stage. This study provides new geochronological evidence for the early developmental history of the West Kunlun orogenic belt.